Sistem Pendukung Keputusan untuk Rekomendasi Kelulusan Siswa di SMK Negeri 13 Medan Menggunakan Metode AHP - Nasution, Alvin Julian Saputra; Budi Triandi (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The graduation process at SMK Negeri 13 Medan has traditionally been conducted through teacher council meetings, where assessments are based on various, often subjective, aspects. Complexity arises because decisions must consider numerous variables—from program fulfillment, student attitudes and behaviors, fieldwork achievements, school exam scores, to cumulative final grades—making manual evaluations prone to inconsistencies and potential unfairness. To address these weaknesses, this study developed a Decision Support System (DSS) utilizing the Analytic Hierarchy Process (AHP) method. AHP was chosen for its ability to formulate qualitative data into a quantitative scale, allowing each criterion to be compared systematically and measurably. The study used a sample of 66 students and assessed five main criteria relevant to determining graduation. The system output was a recommendation for graduation decisions grouped into three alternatives: "Graduate with Good Predicate," "Pass," and "Fail." It is hoped that the implementation of this AHP-based DSS will increase transparency and efficiency in decision-making, reduce subjectivity, and support a more consistent and equitable graduation process within the school environment.